Morphometric features of Scots pine progenies with different resistance to annosum root rot in Kharkiv region - Dyshko, V. A.; Ustsky, I. M.; Torosova, L. O.; Mykhailichenko, O. A. (Forestry and Forest Melioration, 2021)
Introduction Root rot disease caused by Heterobasidion annosum s. l. is one of the most dangerous in Scots pine forests. To date, the causes of pine tree vulnerability to this disease have not been clearly identified. It was suggested that natural regeneration at the pine dieback site, which is the progeny of trees with different resistance to damage (“relatively resistant” and “affected” trees), might be a good alternative for artificial reforestation. The use of high-quality seeds with increased resistance for reforestation of the areas with possible risks of root rot damage can be one of the effective ways to manage the disease. Materials and Methods We studied two-year-old seedlings grown from seeds of Scots pine trees of I and III health condition categories in the greenhouse in Pivdenne Forestry, Kharkiv Forest Research Station. The seeds were harvested from “relatively resistant” and “affected” trees in sites infected by the root rot and control sites. The parameters of seedlings (length, root collar diameter, length, and weight of roots) and needles (length and weight) were measured under laboratory conditions. The results of the study were processed by variation statistics method using Microsoft Excel application. Results Significant advantages of “relatively resistant” trees over “affected” ones were revealed by the average length of seedlings (15%), the proportion of their underground part (8%), and the mass of the roots (15%). The collar root diameters did not differ significantly (3–6%) in the variants within the experiment. The proportion of seedlings of “relatively resistant” trees with weak roots was 36.4%; the seedling with vigorous roots made 42.3% and with very large roots 21.2%. Among the samples of “affected” trees, most seedlings, 57.6%, had a weak root system; 24.2% and 18.2% of the seedlings had vigorous and very large roots, respectively. Two-year-old seedlings of “relatively resistant” trees had shorter lengths and lower weights of needles (17% and 23%, respectively), as compared to “affected” ones. Among the seedlings of “relatively resistant” trees, specimens with short and medium needles predominated (43.2% and 51.4%, respectively). For “affected” seedlings, medium- and long-needle ones predominated (54.5% and 30.3%, respectively). The weight of 100 needles of “relatively resistant” tree seedlings was 23% less than that of “affected”. Seedlings of “relatively resistant” trees, in contrast to “affected”, had lower limit values of needle length and greater variation (Cv = 22.2%; Cv = 17.2%, respectively). In the control, the range of values was larger than in the experimental variants, and the variability of the indicators was higher (Cv = 25.4%). Conclusions The most essential factor that allows seedlings to better adapt to environmental conditions and the impact of adverse factors is the root vigor, which is probably the main qualitative characteristic that allows them to survive in a highly pathological background. The obtained results indicate the saving of hereditary traits of resistance to the root rot disease in about 20% of seed offspring. Given the advantages of seeds from “relatively resistant” trees, it is advisable to use them for reforestation.